EVALUASI TAX PLANNING: STUDI KASUS PADA PT BUKIT ASAM (PERSERO) Tbk. - , DANNA ATMOKO; , Slamet Sugiri, Prof. Dr., M.B.A., C.M.A., Ak ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tax planning is the way to manage a business as one of the taxpayer in its right way based on the rules of taxation to minimize the debt of its tax. The aims of this tax planning are to minimize the burden of tax which being debted so it can maximize the profit after tax and to cover the duty of taxation in the right, efficient, and effective way, which suitable to the provision of taxation. The objectives of this observation is to seek and analize the depreciation of tangibleassets and the amortization of intangible assets in PT Bukit Asam (persero) Tbk. Based on the rules of taxation which can be used to minimize the debted tax. The data analysis done by using the report of depreciation reconciliation and fiskal amortization on 2012 which then be evaluated based on UU no.36 year 2008 about income tax.